Marvellous Ecologies: The Twilight World(s) of Gabríela Friðriksdóttir - Sólveig Guðmundsdóttir (Approaching religion, 2025)
In this article I examine how ecological and esoteric knowledge intersects in the works of the contemporary Icelandic artist Gabríela Friðriksdóttir. Drawing from diverse traditions and practices, such as alchemy, Neopaganism, tarot, numerology and animism, she uses and reinterprets esoteric knowledge and iconography to build her own worlds. Following this analysis, I place Gabríela's works within art history, notably in relation to the esoteric and ecological perspectives found in Surrealism. Here I specify this investigation by examining her fusion of interior life and exterior worlds through the lens of the surreal marvellous. Gabríela proposes expanding our perspectives on humans, non-humans and the environment we share, exploring new forms of interconnection between these actors. This is a recurring formal and textual theme in her art, one that negates the Western binary systems that have long been implemented to categorise and control the environment and its inhabitants: human/nature, nature/culture, human/non-human, man/woman etc. Gabríela's creations trouble these boundaries, in particular her hybrids that blend human and other-than-human qualities. I further relate this to the lineages of Surrealism and their critique on Western ideologies and systems.